2019
DOI: 10.3390/tropicalmed4030101
|View full text |Cite
|
Sign up to set email alerts
|

Intercepted Mosquitoes at New Zealand’s Ports of Entry, 2001 to 2018: Current Status and Future Concerns

Abstract: Mosquito vectors are extending their range via international travel and trade. Climate change makes New Zealand an increasingly suitable environment for less tropically adapted exotic mosquito vectors to become established. This shift will add a multiplier effect to existing risks of both the establishment of new species and of resident exotic species extending into new areas. We describe trends in the border interceptions of exotic mosquitoes and evaluate the role of imported goods as a pathway for these intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…aegypti with aerial incursions have been noted at New Zealand ports. 17 Considering the broad sympatry of these species throughout the Indo-Pacific, 43 these findings raise questions about why marine incursions are relatively rare for Ae. aegypti and why aerial incursions are relatively rare for Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aegypti with aerial incursions have been noted at New Zealand ports. 17 Considering the broad sympatry of these species throughout the Indo-Pacific, 43 these findings raise questions about why marine incursions are relatively rare for Ae. aegypti and why aerial incursions are relatively rare for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and Ae. aegypti both disperse internationally on vessels like ships and aeroplanes, 1719 analysis of their genetic structure in the Indo-Pacific has indicated that gene flow pathways are different in these species. 20 Likewise, interceptions at New Zealand borders found that most Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…populations can spread advantageous alleles that reduce the efficacy of local control programs [ 24 ]. Incursions of these species are frequently linked to vessels such as ships and planes [ 19 , 20 , 25 ], and when source locations can be identified they are often far from the point of collection [ 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti and one adult of Ae. albopictus (Ammar et al, 2019). In general, mosquitoes transported in airplanes are considered less probable to establish due to the low number of adults transported.…”
Section: Aircraft Introductionmentioning
confidence: 99%